Trends in socioeconomic inequalities in anthropometric status in a population undergoing the nutritional transition: data from 1982, 1993 and 2004 pelotas birth cohort studies - Matijasevich, Alicia (BioMed Central, 2012)
BACKGROUND: Socioeconomic inequalities in child nutrition may change rapidly over time, particularly in populations undergoing the nutrition transition. Yet, the few available studies are repeated cross-sectional surveys. By studying three prospective birth cohorts in the same city over a period of more than two decades, we describe secular trends in overweight and stunting at different ages, according to socioeconomic position. METHODS: Population-based birth cohort studies were launched in the city of Pelotas (Brazil) in 1982, 1993 and 2004, with follow-up visits at twelve, 24 and 48 months. Children were weighed and measured at every visit. Z-scores of length/height-for-age and body mass index-for-age were calculated using the WHO Child Growth Standards. The slope and relative indices of inequality, based on family income quintiles, were estimated for each follow-up visit. RESULTS: Between the 1982 and 2004 cohorts, stunting among four-year-olds declined (from 10.9% to 3.6%), while overweight increased (from 7.6% to 12.3%). In every visit, stunting prevalence was inversely related to income. Both absolute and relative inequalities declined over time; among four-year-olds stunting dropped from 26.0% in the 1982 cohort to 6.7% in the 2004 cohort in the poorest group, while in the richest group stunting prevalence dropped from 2.7% in 1982 to 1.1% in the 2004 cohort study. The secular trend towards increased overweight was evident for four-year-olds, in almost all socioeconomic groups, but not among one and two-year-olds. Among four-year old children, overweight prevalence increased in all income quintiles, by 130% in the middle-income group, 64% in the poorest and 41% in the richest group. CONCLUSIONS: The decline in stunting is remarkable, but the increase in overweight among four-year olds – particularly among the poorest and the middle-income groups– requires concerted efforts to prevent the long term consequences of child overweight.